Pengaruh CAR, BOPO, NPL, NIM, dan LDR terhadap ROA pada Perusahaan di Sektor Perbankan yang Terdaftar di BEI Periode 2012-2016 - Aminar Sutra Dewi (JURNAL PUNDI, 2017)
This study aims to examine the relationship between Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), BOPO, Net Interest Margin (NIM), Loan to Deposit Ratio (LDR) for Return On Asstes (ROA). The number of samples used are 9 commercial banks listed on the Indonesia Stock Exchange period 2012-2016. The method used in this study using multiple regression analysis using Eviews 6. From the results of tests performed show that CAR statistically does not significantly influence tehadap ROA, BOPO significantly influence teh ROA, NPL has significant effect to ROA, different from NIM which has no significant effect on ROA, and LDR has significant effect on ROA. Keywords: CAR, BOPO, NPL, NIM, LDR and ROA